Analysis of The Impact of Almsgiving on The Economic Welfare of The Community: A Case Study in Indonesia - Syarifuddin; Aswan; Andi Muh. Taqiyuddin BN; Nur Ifna (El-Fata: Journal of Sharia Economics and Islamic Education, 2026)
This study aims to analyse the impact of charity on community welfare, using a case study in Indonesia. The study is qualitative in nature. The research design is a literature review. The findings indicate that charity plays a role in economic development in the short term through its consumptive function and in the long term through its productive function. Nevertheless, there are still those who are reluctant to give charity. There are internal and external factors that may influence charitable giving behaviour. This indicates that charitable giving behaviour can be influenced by various factors. Charitable giving can have a widespread and long-term impact. The theoretical implications of this research are that it can serve as a reference in understanding the concept of the impact of charity on community welfare in Indonesia. As for the practical implications of this research, it can serve as a reference in the management of charity that impacts community welfare in Indonesia